Fertilizer use among cocoa farmers in Ghana: the case of Sefwi Wiawso District - Nunoo, Isaac; Frimpong, Benedicta Nsiah; Frimpong, Frederick Kwabena (International Journal of Environment, 2014)
This study analyses factors that influence fertilizer use among cocoa farmers in the Sefwi Wiawso District in the Western Region, Ghana. Primary data were obtained from 200 cocoa farmers in the district. Descriptive statistics and ordinary least square regression analysis were used to analyse data collected. The results revealed that majority of the cocoa farmers were males and are getting old. Also farm size and price of fertilizer were significant factors affecting fertilizer use among cocoa farmers in the Sefwi Wiawso District in the Western Region. Moreover 74.5 percent farmers do not use fertilizer whereas 25.5 percent use fertilizer on their cocoa farms. The study recommends that Ghana government should further subsidise the price of fertilizer to make fertilizer more affordable to small holder cocoa farmers and also adopt strategies that hedge against price risk. In addition, illiterate farmers should be encouraged to undergo adult literacy programmes. Rural development policies should think about the importance of improving small-scale farmers? access to credit market. Furthermore, the extension unit of the Ghana Cocoa board and Ministry of Agriculture should be strengthened to educate cocoa farmers more on fertilizer usage. DOI: http://dx.doi.org/10.3126/ije.v3i1.9939 International Journal of Environment Vol.3(1) 2014: 22-31